Influence of Place Attachment, Perceived Value, and Personal Norms on Tourist Environmentally Responsible Behavior at Indonesia's Super Priority Destinations - Kennedy, Cindy Fieroncia (Student Journal of Business and Management, 2023)
The purpose of this study is to examine how the effect of place attachment, perceived value, personal norms toward tourist environmentally responsible behavior on five Super Priority Destinations in Indonesia. The measurement of this study used 28 indicators items and distributed using an online questionnaire. The total sample in this study was 271 respondents and data were analyzed using SEM PLS (Partial Least Square). Based on data analysis, the result obtained that; (1) place attachment influences perceived value, (2) place attachment influences tourist environmentally responsible behavior (3) personal norms influence tourist environmentally responsible behavior, (4) perceived value influences tourist environmentally responsible behavior, (5) perceived value mediates between place attachment and environmentally responsible tourist behavior. This research contributes to the literature on tourist behavior.